Development and validity of an innovative test to assess guideline-consistent clinical reasoning by physical therapists in stroke rehabilitation - Nicoline M. Otterman; Marjo Maas; Sven K. Schiemanck; Philip van der Wees; Gert Kwakkel (Medical Journals Sweden, 2019)
Objective: To evaluate the validity of a script concordance test to assess guideline-consistent clinical reasoning by physical therapists in stroke rehabilitation, and to identify critical features of physical therapists specializing in stroke rehabilitation. Methods: A script concordance test was developed according to current standards. Four subgroups of physical therapists (those specializing in neurology, those focusing on neurology or geriatrics, other, and non-specialized undergraduate students) were asked to complete the test. The construct validity of the script concordance test was evaluated with 1-way analysis of variance (ANOVA) to estimate differences between subgroups. Associations between physical therapist characteristics, and script concordance test scores were analysed with bivariate regression analysis followed by multivariate analyses. Results: The script concordance test, with 59 items, was completed by 211 physical therapists. ANOVA analysis showed statistically significant differences between the script concordance test scores of the 4 groups (p < 0.001), with higher scores by the physical therapists specializing in neurology compared with the other, non-specialized, subgroups. The multivariate analysis showed that better guideline knowledge (B = 1.07; CI = 0.48-1.65; p = <0.001), successful completion of the Dutch Neurorehabilitation course (B = 4.1; CI = 1.37-6.87; p = 0.003), and participation in professional development activities (B = 2.4; CI = 0.05-4.68; p = 0.046) were associated with higher script concordance test scores. Conclusion: The script concordance test has good construct validity. Greater self-reported guideline knowledge, successful completion of the post-bachelor Dutch Neurorehabilitation course, as well as systematic participation in professional development activities facilitate important factors that enhance specialization. The script concordance test is a valid feedback tool for physical therapists to support professional development in the domain of stroke rehabilitation.